INTERTEXTUALITY OF THE COVID-19 ON FACEBOOK COMMENTS - Gultom, Fajar Natalia Br (Quaerite Veritatem : Jurnal Pendidikan, 2022)
Covid-19 is becoming a hot issues for wrold-wide. It is obtaining all news items in the world. Started from goverment policy, telivision upto all social media. in order to view how people express their claim toward Covid-19 effect on society the writer make simple inter textual analysis on Facebook comment. The data base is taken from 10 comments of Facebook groups users and then analyzed them with using qualitative descritive method. The point focuses on Intertextuality types by Fitzsimmons (2013). They are Obligatory, Optional, and Accidental Intertextuality senses on the Facebook comment related to Covid-19 and identify the most dominant types presented on the Facebook column and see relationship toward real situation right now. In order to make systematic study the writer use observation teory. The result there are five types of Optional Intertextuality, three types of Accidental Intertextuality, and two types of Obligatory Intertextuality. It is happened as the effect of Covid-19 has make the people in danger situation.